2022
DOI: 10.3389/fbioe.2022.947616
|View full text |Cite
|
Sign up to set email alerts
|

Novel Photo- and Thermo-Responsive Nanocomposite Hydrogels Based on Functionalized rGO and Modified SIS/Chitosan Polymers for Localized Treatment of Malignant Cutaneous Melanoma

Abstract: Melanoma is an aggressive type of skin cancer that accounts for over 75% of skin cancer deaths despite comprising less than 5% of all skin cancers. Despite promising improvements in surgical approaches for melanoma resection, the survival of undetectable microtumor residues has remained a concern. As a result, hyperthermia- and drug-based therapies have grown as attractive techniques to target and treat cancer. In this work, we aim to develop a stimuli-responsive hydrogel based on chitosan methacrylate (ChiMA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The obtained smart therapeutic hydrogel was evaluated for its chemo/photothermal therapy, drug release, and biocompatibility, and the results revealed the capability of generating local hyperthermia and releasing DOX under NIR irradiation (Figure 3). The cytotoxicity tests demonstrated that, with the photo-induced release of DOX, cell death occurred, suggesting the cytotoxic effect of SISMA/CSMA/rGO-DOX smart hydrogel [77]. Nowadays, for cancer-related applications, injectable hydrogels have been receiving great attention because of their special properties.…”
Section: Cancer Photothermal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained smart therapeutic hydrogel was evaluated for its chemo/photothermal therapy, drug release, and biocompatibility, and the results revealed the capability of generating local hyperthermia and releasing DOX under NIR irradiation (Figure 3). The cytotoxicity tests demonstrated that, with the photo-induced release of DOX, cell death occurred, suggesting the cytotoxic effect of SISMA/CSMA/rGO-DOX smart hydrogel [77]. Nowadays, for cancer-related applications, injectable hydrogels have been receiving great attention because of their special properties.…”
Section: Cancer Photothermal Therapymentioning
confidence: 99%
“…Photothermal heating of S2C1 and S2C1GO during ( C ) a first therapy cycle (T1) and ( D ) subsequent second (T2) and third (T3) therapy cycles. ( E ) Concentration of DOX released from S2C1GO for the different therapies using simulations (in silico) and unirradiated hydrogels with (w/) and without (w/o) ascorbic acid (aa) as positive and negative controls [ 77 ] (Copyright 2022 Creative Commons: Céspedes-Valenzuela, Sánchez-Rentería, Cifuentes, Gómez, Serna, Rueda-Gensini, Ostos, Muñoz-Camargo, and Cruz, doi:10.3389/fbioe.2022.947616).…”
Section: Figurementioning
confidence: 99%
“…Therefore, when designing new strategies to treat cancer photothermally using GBNMs, researchers should consider the NIR-II region for irradiation. Pd@PPy/GO MCF-7 808 nm; 1.5 W/cm 2 30 (∆T) [82] PTX@GO-PEG-OSA Gastric cancer 808 nm; 1.0 W/ cm 2 43 [83] GO-FA/Ce6 MCF-7 808 nm; 2.0 W/cm 2 17 (∆T) [75] nGO-PEG-ARS HepG2 808 nm; 2.0 W/cm 2 60 [73] fGO@GNRs-DOX HeLa and A549 808 nm; 1.0 W/cm ICG@MS-rGO-FA Colorectal 808 nm; 1.0 W/cm 2 26 (∆T) [85] nGO-PEG Colon 808 nm; 1.5 W/cm 2 47 (∆T) [86] GO@SiO2@AuNS KM12C 808 nm; 0.3 W/cm 2 16 (∆T) [87] nGO-COS-CD47/DTIC Melanoma 808 nm; 2.0 W/cm 2 55 [88] GO-v50-DOX Melanoma 808 nm; 7.0 W/cm 2 54 [89] rGO-AuNS, rGO-AuNR HUVECs 808 nm; 3.0 W/cm 2 57 (∆T) [90] Abbreviations: AuNS (gold nano star particle); DODAB/DOPE (bromide/1,2-dioleoyl-sn-glycero-3phosphoethanolamine); RSV (resveratrol); PNIPAM (poly(N-isopropylacrylamide); AAM (allylamine); PPy (polypyrrole); PTX (paclitaxel); PEG (polyethylene glycol); OSA (oxidized sodium alginate); FA (folic acid); Ce6 (chlorin e6); ARS (artesunate); GNRs (gold nanorods); AGD (graphene oxide (GO)-hybridized nanogels); ICG (indocyanine green); SN (7-ethyl-10-hydroxycamptothecin (SN-38)); MS (mesoporous silica); CD47 (is an antibody); COS (chitosan oligosaccharide); DTIC (dacarbazine); v-50 (azo initiator); AuNR (gold nanorod).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Some studies have shown that the polymer hydrogel formed by the co‐assembly of reduced graphene oxide functionalized DOX, porcine small intestinal submucosa methacrylate (SISMA), and chitosan methacrylate (ChiMA) had the ability to release drug DOX in both light and thermo response. [ 98 ] The generation of heat under NIR light irradiation could further stimulate the release of DOX, while PTT could enhance the suppression of tumors, allowing the SISMA/ChiMA/rGO composite hydrogel to effectively treat melanoma tumors. The dual external triggers could on demand control the drug release at the local site, which not only improved the drug delivery efficiency but also provided a new pathway for synergistic chemotherapy, PTT, and PDT.…”
Section: Dual‐responsive Nanocarriersmentioning
confidence: 99%